POST-MINING LAND CHARACTERISTICS AND REHABILITATION TECHNIQUE IN BANGKA AND SINGKEP ISLANDS - SITORUS, SANTUN R.P; KUSUMASTUTI, E.; BADRI, L. NURBAITI (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2008)
Post-mining land has generally unfavourable characteristics for a growing media for crops. The objectives of the present study were: (1) to study natural changing of soil physical and chemical properties and natural vegetation of four different ages of tailing, (2) to study rehabilitation technique of post mining tailing for forest crops, and (3) to study effects of ameliorant on soil physical and chemical properties, and heavy metal content on four different ages of tailing. Analysis of tailing characteristics, in situ natural vegetation analysis and two sets of green house experiments had been done. The two greenhouse experiments comprise: (1) tailing from Sungai Liat Bangka with two factors, those are three level applications of organic matter and mineral soil with teak as an indicator plant and (2) tailing from Dabo Singkep with treatments: tailing + compost 9:1,tailing + animal manure 9:1 and tailing as control, CMA inoculant and forest trees akasia (Acacia auriculiformis), gamal (Gliricidia maculata), lamtoro (Leucaena leucocephala) and sengon or jeungjing (Paraserianthes falcataria). The result showed that: generally, tin mining reduce soil quality and number of natural vegetation. The soil characteristics and number of vegetation are generally increase (getting better) with time. The first greenhouse experiment showed that the best response of teak plant was under combination of organic mater and soil mineral whereas ameliorant proportion factor is not significantly different. The second greenhouse experiment showed that the treatments were significantly influencing canopy diameter, leaf number, root length and tree trunk circle, respectively. The best rehabillitation technique was combination of animal manure, mycorrhizal inoculants treatments and lamtoro (L. leucocephala). Soil characteristics and heavy metal contents were significantly influenced by ameliorant and tailing ages. Soil chemical properties were significantly influenced by tailing age, types and proportions of ameliorant. The Fe, Mn, Cu, Pb, and Sn of soil were significantly influenced by tailing ages and the highest was on the six years tailing.